Teacher shortage in Sweden: time to take action? - Marcia Håkansson Lindqvist; Lena Boström; Ulrika Gidlund (University of Aberdeen, School of Education, 2022)
In Sweden, the lack of teachers is a national challenge and a societal problem, and the difference between supply and demand for teacher students will increase until 2035. Today, only 7 out of 10 teachers in compulsory school have certification and the variation between schools and regions is great. The overall aim of this article is to explore and analyse the current state of teacher shortage in Sweden. Document analysis was used for reviewing, evaluating and analysing documents, and constructionist thematic analysis was adopted. The results show that there are many different, overlapping or similar factors behind the Swedish teacher shortage and are related to reforms, retention and recruitment. Several curriculum and teacher education reforms have changed and deteriorating work environments and have led to many dropouts for the profession. Low status and the constant poor picture the media portray of Swedish schools and teachers have a strong impact on Sweden's teacher shortage. Further, political reforms on communalization, decentralization, teacher certification and privatization of schools have changed the structural conditions. Therefore, we call for a change in the attitude towards the teaching profession. Thus, this article provides insights for teachers, teacher educators, policy makers and other stakeholders on the national and international level.